Thread-like adhesive body
Patent Information
- Application Number
- JP2020162686
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2020-09-28
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-09-28
AI Technical Summary
【0009】 本発明の糸状粘着体は、強度や柔軟性の確保と、環境負荷の低減を両立している。
Smart Images

Figure 0007640242000002 
Figure 0007640242000003 
Figure 0007640242000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a thread-like adhesive body. [Background technology]
[0002] When bonding articles together, an adhesive body having a substrate and an adhesive layer may be used in order to prevent dripping, etc. As an example of an adhesive body, an adhesive tape having an adhesive layer formed on one surface of a substrate is known. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2009-173715 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, there has been a strong demand for reducing the environmental burden in order to realize a sustainable society, and there is also a demand for improving the biomass content of adhesives. Here, methods for improving the biomass degree of the adhesive body include a method for improving the biomass degree of the substrate and a method for improving the biomass degree of the adhesive layer. However, improving the biomass degree of the adhesive layer may lead to a decrease in adhesive strength and an increase in manufacturing costs. Therefore, in order to improve the biomass degree of the adhesive body, it is particularly desirable to improve the biomass degree of the substrate.
[0005] However, many materials containing components derived from biomass (biomass materials) are hard and brittle, and therefore, when the substrate of an adhesive tape as described above is made from biomass, the strength and flexibility are likely to decrease.
[0006] To address such problems, in Patent Document 1, various properties such as strength are improved by adding an additive made of a non-biomass material to polylactic acid, which is a biomass material. However, in the film described in Patent Document 1, a large amount of non-biomass material is added to the biomass material, and therefore, a sufficiently high biomass content cannot be obtained with such a film.
[0007] The present invention has been made in view of the above, and has an object to provide an adhesive body that ensures strength and flexibility while reducing the environmental load. [Means for solving the problem]
[0008] The thread-like adhesive of the present invention, which solves the above-mentioned problems, is a thread-like adhesive comprising a thread-like core material and an adhesive layer covering the longitudinal surface of the core material, wherein the core material contains a biomass-derived component and the biomass degree of the thread-like adhesive is 35% or more. In one embodiment of the thread-like adhesive material of the present invention, the contact angle θ0 of water measured immediately after 2 μl of water is dropped onto the core material, and the contact angle θ of water measured 30 seconds after the dropping 30 Difference between (θ0-θ 30 ) may be 20° or less. In one embodiment of the thread-like adhesive material of the present invention, the core material may be a multifilament thread. In one embodiment of the thread-like cohesive body of the present invention, the multifilament yarn may comprise filaments that are free of biomass-derived components. In one embodiment of the thread-like adhesive of the present invention, the multifilament thread may be twisted. Effect of the Invention
[0009] The thread-like adhesive material of the present invention ensures strength and flexibility while reducing the environmental load. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a cross-sectional view of a thread-like adhesive body according to one embodiment of the present invention, taken along a cross section perpendicular to the longitudinal direction. [Diagram 2] FIG. 2 is a schematic diagram for explaining a method for measuring θ0 and θ30. [Diagram 3] FIG. 3(a) is a perspective view for explaining a method for evaluating the adhesive strength of a thread-like adhesive body of the present invention, and FIG. 3(b) is a cross-sectional view taken along line AA in FIG. 3(a). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the thread-like adhesive body of the present invention will be described in detail. Note that the present invention is not limited to the embodiment described below. In addition, in the drawings, members and parts having the same function may be described with the same reference numerals, and duplicated descriptions may be omitted or simplified. In addition, the embodiments shown in the drawings are schematic in order to clearly explain the present invention, and do not necessarily accurately represent the size or scale of the actual product.
[0012] [Thread-like adhesive substance] FIG. 1 shows a cross-sectional view of a thread-like adhesive body 10 according to one embodiment of the present invention, taken along a line perpendicular to the longitudinal direction. The thread-like adhesive body 10 of this embodiment is a thread-like adhesive body including a thread-like core material 2 and an adhesive layer 1 that covers the surface of the core material 2 in the longitudinal direction. In this embodiment, the core material contains a biomass-derived component. Moreover, the thread-like adhesive body of this embodiment has a biomass ratio of 35% or more.
[0013] In this specification, thread-like means a shape in which the longitudinal length is sufficiently long compared to the width length, and the ratio of the length of the long axis (the longest axis passing through the center of gravity of the cross-sectional shape) to the length of the short axis (the shortest axis passing through the center of gravity of the cross-sectional shape) in a cross-sectional shape perpendicular to the longitudinal direction (hereinafter also referred to as the "cross-sectional shape") (long axis / short axis) is, for example, 200 or less, preferably 100 or less, more preferably 50 or less, even more preferably 10 or less, still more preferably 5 or less, and particularly preferably 3 or less, and also means a state in which it can be bent in various directions and angles like a thread.
[0014] In this specification, a biomass-derived component refers to a component derived from a renewable organic resource. Typically, it refers to a component derived from a biological resource that can be reproduced sustainably in the presence of sunlight, water, and carbon dioxide. Therefore, it excludes components derived from fossil resources that are depleted through use after mining (fossil resource-based materials). For example, a component derived from a plant is a biomass-derived component. Moreover, the non-biomass-derived components refer to components other than the biomass-derived components.
[0015] The biomass degree of a thread-like adhesive body is the ratio of the mass of the biomass-derived components contained in the thread-like adhesive body to the total mass of the thread-like adhesive body, and is calculated using the following formula: The same applies to the biomass degrees of the core material and adhesive, which are each calculated using the following formula: Biomass content of thread-like adhesive bodies [%] = 100 × (mass of biomass-derived components contained in thread-like adhesive bodies [g]) / (total mass of thread-like adhesive bodies [g]) Biomass content of core material [%] = 100 × (mass of biomass-derived components contained in core material [g]) / (total mass of core material [g]) Biomass content of adhesive [%] = 100 × (mass of biomass-derived components contained in adhesive [g]) / (total mass of adhesive [g]) The biomass degree can also be measured, for example, in accordance with ASTM D6866-18.
[0016] The present inventors have conducted extensive research and have found that in an adhesive body using a substrate containing a biomass-derived component, flexibility can be imparted to the substrate by using a filamentous core material as the substrate, and fragility can be compensated for by covering the longitudinal surface (circumferential surface) of the core material with an adhesive layer. In other words, the present inventors have found that a filamentous adhesive body including a filamentous core material containing a biomass-derived component and an adhesive layer covering the longitudinal surface of the core material can ensure strength and flexibility while reducing the environmental load, and have completed the present invention.
[0017] The biomass degree of the thread-like adhesive body is set to 35% or more from the viewpoint of reducing the environmental load. It is also preferably 50% or more, more preferably 70% or more, even more preferably 90% or more, and most preferably 100%. The biomass degree of the thread-like adhesive body can be adjusted by adjusting the biomass degree of the core material and / or the adhesive layer. In the thread-shaped adhesive of this embodiment, the deterioration in strength and flexibility, which is a drawback caused by turning the base material into biomass, is eliminated by making the core material into a thread and coating it with an adhesive layer as described above, so that it is possible to achieve both the high biomass level as described above and strength and flexibility.
[0018] On the other hand, if the biomass degree of the core material or the adhesive layer is increased too much in order to increase the biomass degree of the thread-like adhesive body, problems such as reduced strength and flexibility, reduced adhesive power, increased production costs, etc. Therefore, the biomass degree of the thread-like adhesive body is preferably 95% or less, more preferably 90% or less, and even more preferably 80% or less.
[0019] Furthermore, the inventors have conducted extensive research and found that when threads that are easily permeated with adhesive, such as cotton threads, are used as the core material in a thread-like adhesive, the adhesive permeates and adheres not only to the outer surface of the core material, which contributes to the adhesiveness, but also to the inside of the core material, and therefore a large amount of adhesive must be used to achieve sufficient adhesive strength. Since adhesives usually have a lower biomass degree than core materials, increasing the amount of adhesive used leads to a decrease in the biomass degree of the entire thread-like adhesive. Therefore, from the perspective of reducing environmental impact, it is preferable to use a core material that is less permeated with adhesive.
[0020] As an index for evaluating the ease of penetration of the adhesive into the core material, the contact angle θ0 of the water measured immediately after dropping 2 μl of water onto the core material and the contact angle θ of the water measured 30 seconds after dropping were used. 30 Difference between (θ0-θ 30 The larger the contact angle difference, the more easily the adhesive will penetrate into the core material, and therefore a large amount of adhesive will be required to ensure sufficient adhesive strength, making it difficult to improve the biomass degree. Therefore, the contact angle difference (θ0-θ 30 The contact angle difference (θ0-θ) is preferably 20° or less, more preferably 15° or less, further preferably 10° or less, and particularly preferably 5° or less. 30 ) is not particularly limited, and may be 0°. The difference in contact angle (θ0-θ 30 ) can be controlled, for example, by appropriately changing the material of the core material. In general, when the core material contains a lot of short fibers, a lot of fibrils, or a lot of air, the contact angle difference (θ0 - θ 30 Therefore, for example, the thickness tends to be smaller if a yarn containing a large amount of long fibers or a yarn with few fibrils is used as the core material, or if the core material is twisted.
[0021] The difference in contact angle (θ0-θ 30 As shown in FIG. 2, two 2 cm thick acrylic plates 3 are arranged with a gap of 3 cm between them, and a core material 2 is stretched straight across the gap on the top surfaces of these acrylic plates and attached with tape 4. Next, 2 μl of water is dropped onto the core material that spans the gap, and the contact angle of water θ0 immediately after the drop and the contact angle of water θ after 30 seconds have passed are measured. 30 can be calculated from the values measured using a contact angle meter (for example, product name "DropMaster" manufactured by Kyowa Interface Science Co., Ltd.).
[0022] The core material is thread-like, contains biomass-derived components, and has a biomass content of 35% or more for the entire thread-like adhesive body. There are no particular limitations on its shape or material, and these may be adjusted appropriately depending on the required properties such as strength, mass, hardness, etc.
[0023] The cross-sectional shape of the core material is typically circular, but may be various other shapes such as elliptical or polygonal. The thickness of the core material is not particularly limited, and may be appropriately adjusted together with the thickness of the adhesive layer so that the thickness of the thread-like adhesive body is appropriate depending on the application. For example, the thickness of the thread-like adhesive body is set to 5 to 3000 μm.
[0024] The core material may be a monofilament consisting of a single filament, or a multifilament yarn consisting of multiple filaments. It may also be a spun yarn, a processed yarn that has been subjected to crimping or bulking processing, generally referred to as a textured yarn, bulky yarn, or stretch yarn, a hollow yarn, or a yarn that is a combination of these by twisting them together, etc. When the core material is a multifilament yarn, all of the filaments constituting the multifilament yarn may contain a biomass-derived component, or only some of the filaments may contain a biomass-derived component, and the other filaments may not contain a biomass-derived component. By adjusting the ratio of the number of filaments containing a biomass-derived component to the number of all filaments constituting the multifilament yarn, various properties such as the degree of biomass, resistance to penetration of adhesive, and strength can be easily adjusted. Furthermore, although yarns containing biomass-derived components tend to have low flexibility, by using a multifilament yarn as the core material, the individual filaments that make it up become thinner, improving flexibility. Therefore, multifilament yarns are preferable from the viewpoint of improving flexibility as well. The number of filaments constituting the multifilament yarn is not particularly limited and may be appropriately adjusted depending on the application and desired properties of the thread-like adhesive body, but for example, it is preferably 4 or more, more preferably 10 or more, even more preferably 15 or more, and particularly preferably 20 or more. Also, it is preferably 300 or less.
[0025] The multifilament yarn may be a twisted yarn that has been twisted, or may be an untwisted yarn that has not been twisted. In order to further suppress the penetration of the adhesive into the core material, it is preferable that the core material is a twisted multifilament yarn. When the multifilament yarn is twisted, the number of twists is not particularly limited as long as it is more than 0 times / m, but is preferably 30 times / m or more, more preferably 60 times / m or more, and even more preferably 90 times / m or more. On the other hand, if the number of twists is too high, the flexibility of the thread-like adhesive body may be impaired, so that the number of twists is preferably 3000 times / m or less, more preferably 1500 times / m or less, even more preferably 800 times / m or less, and particularly preferably 250 times / m or less.
[0026] The core material is thread-shaped, contains biomass-derived components, and the material constituting it is not particularly limited as long as the biomass content of the entire thread-shaped adhesive body can be 35% or more, and may be appropriately selected depending on the desired biomass content, strength, mass, hardness, etc.
[0027] Examples of materials containing biomass-derived components include natural fibers, such as plant fibers such as hemp, and animal fibers such as silk and wool. Furthermore, examples of materials containing biomass-derived components include biomass plastics, which are broadly classified into those made of biomass-derived components and those made of both biomass-derived components and fossil resource-derived components. Examples of biomass plastics made from biomass-derived components include polyesters (bio-PEs) such as polylactic acid, polyethylene (bio-PE), nylon 11 (bio-PA11), nylon 1010 (bio-PA1010), and polyethylene terephthalate (bio-PET). Examples of biomass plastics made from biomass-derived components and fossil resource-derived components include polyethylene terephthalate (bio-PET), polybutylene succinate (bio-PBS), polybutylene terephthalate succinate, polyamide 610, 410, 510, 1012, 10T, 11T, MXD10 (bio-PA610, 410, 510, 1012, 10T, 11T, MXD10), polycarbonate (bio-PC), polyurethane (bio-PU), aromatic polyester, unsaturated polyester, phenolic resin, epoxy resin, polylactic acid blend / PBAT, starch blend / polyester resin, etc. From the viewpoint of making it difficult for the adhesive to soak into the core material, polyester and polyethylene, which are difficult to be impregnated with moisture, are particularly preferable.
[0028] From the viewpoint of reducing the environmental burden, the biomass ratio of the core material is preferably 25% or more, more preferably 50% or more, even more preferably 70% or more, and most preferably 100%. On the other hand, if the biomass degree of the core material is increased too much, problems such as reduced strength and flexibility, reduced adhesive strength, increased manufacturing costs, etc. Therefore, the biomass degree of the core material is preferably 95% or less, more preferably 80% or less, and even more preferably 70% or less.
[0029] The core material may contain various additives, such as fillers (inorganic fillers, organic fillers, etc.), antioxidants, antioxidants, UV absorbers, antistatic agents, lubricants, plasticizers, colorants (pigments, dyes, etc.), etc. The surface of the core material may be subjected to a known or conventional surface treatment, such as a corona discharge treatment, a plasma treatment, or application of a primer.
[0030] In addition, in the thread-like adhesive body having a core material, the core material does not necessarily have to be entirely covered with the adhesive layer, and may have a portion that does not have the adhesive layer as long as the effect of the present invention is achieved. In addition, the end surface of the core material may or may not be covered with the adhesive layer. For example, when the adhesive body is cut during the manufacturing process or during use, the end surface of the core material may not be covered with the adhesive layer.
[0031] The pressure-sensitive adhesive layer can be obtained, for example, by applying the pressure-sensitive adhesive composition to the surface of the core material by dipping, immersion, coating, etc., and drying by heating as necessary. The pressure-sensitive adhesive composition can be applied using a conventional coater such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, or a spray coater.
[0032] The type of adhesive composition is not particularly limited. For example, acrylic adhesives, rubber adhesives, vinyl alkyl ether adhesives, silicone adhesives, polyester adhesives, polyamide adhesives, urethane adhesives, fluorine adhesives, epoxy adhesives, etc. can be used. Among them, from the viewpoint of adhesion, rubber adhesives and acrylic adhesives are preferred, and acrylic adhesives are particularly preferred. Note that the adhesive composition may be used alone or in combination of two or more types.
[0033] Acrylic adhesives are mainly composed of polymers of monomers consisting of alkyl (meth)acrylate esters such as ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, and isononyl acrylate, to which modifying monomers such as acrylonitrile, vinyl acetate, styrene, methyl methacrylate, acrylic acid, methacrylic acid, maleic anhydride, vinylpyrrolidone, glycidyl methacrylate, dimethylaminoethyl methacrylate, hydroxyethyl acrylate, acrylamide, and γ-methacryloxypropyltrimethoxysilane may be added as necessary.
[0034] Rubber-based adhesives are based on rubber polymers such as natural rubber, styrene-isoprene-styrene block copolymer, styrene-butadiene-styrene block copolymer, styrene-ethylene-butylene-styrene block copolymer, styrene-butadiene rubber, polybutadiene, polyisoprene, polyisobutylene, butyl rubber, chloroprene rubber, and silicone rubber.
[0035] In addition, these pressure-sensitive adhesive compositions can be appropriately blended with various additives such as tackifying resins such as rosin-based, terpene-based, styrene-based, aliphatic petroleum-based, aromatic petroleum-based, xylene-based, phenol-based, coumarone-indene-based, and hydrogenated versions of these resins, as well as crosslinking agents, viscosity modifiers (thickeners, etc.), leveling agents, release regulators, plasticizers, softeners, fillers, colorants (pigments, dyes, etc.), surfactants, antistatic agents, preservatives, antioxidants, UV absorbers, antioxidants, and light stabilizers.
[0036] The adhesive composition may also contain a biomass-derived component. However, if the adhesive composition has too high a biomass ratio, it may lead to a decrease in adhesive strength or an increase in production costs. Therefore, it is preferable that the biomass ratio of the adhesive layer is smaller than that of the core material.
[0037] The adhesive may be either a solvent-based adhesive or a water-dispersed adhesive. Water-dispersed adhesives are preferred because they can be applied at high speed, are environmentally friendly, and have little effect on the core material (swelling, dissolution) due to the solvent.
[0038] In the thread-like adhesive body, from the viewpoint of adhesive strength, it is preferable that a large amount of adhesive is attached to the core material, and specifically, the amount of adhesive attached (mass of adhesive layer per unit length) is preferably 2 mg / m or more, more preferably 5 mg / m or more, and even more preferably 8 mg / m or more. On the other hand, if the amount of adhesive attached is excessive, the adhesive needs to be applied to the core material multiple times in the manufacturing process, and it takes time to dry the applied adhesive, resulting in low manufacturing efficiency. In addition, it is difficult to improve the biomass degree. Therefore, the amount of adhesive attached is preferably 200 mg / m or less, more preferably 180 mg / m or less, and even more preferably 160 mg / m or less.
[0039] The thread-like adhesive may be provided with a separator on the surface of the adhesive layer to protect the adhesive surface until use, but since the separator is discarded when the thread-like adhesive is used, it is preferable not to provide a separator from the standpoint of reducing the environmental burden.
[0040] The thread-like adhesive can be attached to thin components or narrow areas without spilling over, and can be easily applied to complex shapes such as curves, curved surfaces, and uneven surfaces.It is also preferable because it can be easily disassembled (reworked). For example, the thread-like adhesive can be suitably used for fastening articles in the manufacture of electronic devices, and can be applied to fastening narrow frames of mobile terminals such as mobile phones and smartphones.
[0041] In addition, for example, when an adhesive tape is applied to an adherend having a complex shape such as a curve, a curved surface, or an uneven surface, wrinkles or overlaps may occur in the adhesive tape at such a portion, making it difficult to prevent the tape from protruding and to apply the tape neatly. In addition, the wrinkled or overlapped portion may cause a decrease in adhesive strength. In addition, in order to apply the adhesive tape without causing wrinkles or overlaps, it is possible to apply the tape while cutting it into small pieces, but this significantly deteriorates workability. On the other hand, if the thread-like adhesive body is applied to a portion having a complex shape such as a curve, a curved surface, or an uneven surface, it can be firmly applied without causing wrinkles or overlaps. Furthermore, since such a thread-like adhesive body can be applied to the desired portion at once, i.e., in one process, it is excellent in workability and can be applied to an automated line. Specifically, the thread-like adhesive can be suitably used for fixing various wires (linear members) such as electric wires and optical fibers, LED fiber lights, optical fiber sensors such as FBG (Fiber Bragg Gratings), threads, strings, wires, and other thin members in a desired shape. Even when a wire or thin member is fixed to another member in a complex shape, the thread-like adhesive can be used to firmly fix the wire or thin member with excellent workability while suppressing protrusion, wrinkles, and overlaps according to the complex shape that the wire or thin member should have. In addition, when fixing a wire or thin member to another member, the thread-like adhesive can be attached in advance according to the shape of the wire or thin member to be fixed on the surface of the other member, and then the wire or thin member can be attached to the thread-like adhesive attached to the surface of the other member. Alternatively, the thread-like adhesive may be attached to the wire or thin member, and then the wire or thin member may be fixed to the other member in a desired shape.
[0042] The thread-like adhesive can also be suitably used for the purpose of temporarily fixing (temporarily fastening) an article to the surface of another article. More specifically, the thread-like adhesive can be used for the purpose of temporarily fixing (temporarily fastening) an article when manufacturing textile products such as clothes, shoes, bags, and hats, leather products, etc. However, the purpose is not limited thereto, and the thread-like adhesive can be suitably used for various purposes where temporary fixing (temporarily fastening) is desired. For example, when fixing one article to the surface of another article, the first article is provisionally fixed to the surface of the other article using a thread-like adhesive to position it, and then the two articles are fixed (mainly fixed) by a fixing method such as thermocompression bonding or sewing. In this case, if a thread-like adhesive is used, it is easy to provisionally fix the two articles while avoiding the fixing part provided between the two articles. For example, when sewing textile products or leather products, if provisional fixing is performed using a thread-like adhesive, it is easy to provisionally fix the two articles while avoiding the sewing part, and it is easy to prevent the adhesive from adhering to the needle. Furthermore, as described above, if a thread-like adhesive is used, the two articles can be attached well while minimizing overflow, wrinkles, and overlaps, even if they have complex shapes such as curves, curved surfaces, or unevenness, and furthermore, they can be attached in a single process, making the process easy to work with. Furthermore, even in the case of materials that are easily deformed, such as fabric, cloth, leather, etc. that make up textile products or leather products, by temporarily fixing them using a thread-like adhesive, deformation of the materials due to tension can be suppressed or prevented, resulting in good design after fixing (full fixation). Furthermore, if the adhesive thread is used, it is easy to remove the adhesive thread from between the two articles after they have been fixed together (mainly fixed) as necessary. This prevents the adhesive from spilling out, and effectively prevents deterioration of the design caused by discoloration of the remaining adhesive over time. EXAMPLES
[0043] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples in any way.
[0044] <Example 1> (Preparation of Water-Dispersible Acrylic Adhesive for Forming Adhesive Layer) 40 parts by mass of ion-exchanged water was placed in a reaction vessel equipped with a cooling tube, nitrogen inlet tube, thermometer, and stirrer, and nitrogen substitution was performed by stirring at 60°C for 1 hour or more while introducing nitrogen gas. 0.1 parts by mass of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]n hydrate (polymerization initiator) was added to this reaction vessel. While maintaining the system at 60°C, monomer emulsion A was gradually added dropwise over 4 hours to allow the emulsion polymerization reaction to proceed. As the monomer emulsion A, 98 parts by mass of 2-ethylhexyl acrylate, 1.25 parts by mass of acrylic acid, 0.75 parts by mass of methacrylic acid, 0.05 parts by mass of lauryl mercaptan (chain transfer agent), 0.02 parts by mass of γ-methacryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM-503"), and 2 parts by mass of sodium polyoxyethylene lauryl sulfate (emulsifier) were added to 30 parts by mass of ion-exchanged water and emulsified. After the dropwise addition of the monomer emulsion A was completed, the system was kept at 60°C for another 3 hours, cooled to room temperature, and then the pH was adjusted to 7 by adding 10% ammonia water to obtain an acrylic polymer emulsion (water-dispersed acrylic polymer) A. A tackifier resin emulsion (manufactured by Arakawa Chemical Industries, Ltd., product name "E-865NT") of 24 parts by mass based on solid content was added per 100 parts by mass of the acrylic polymer contained in the acrylic polymer emulsion A. Furthermore, the pH was adjusted to 7.2 and the viscosity to 10 Pa·s using 10% by mass ammonia water as a pH adjuster and polyacrylic acid (manufactured by Toagosei Co., Ltd., product name "Aron B-500") as a thickener. In this way, a water-dispersible acrylic adhesive A for the adhesive layer was obtained.
[0045] (Preparation of adhesive articles) The core material was a ply made of four untwisted polylactic acid yarns (280 dtex, Terramac, manufactured by Unitika Ltd.) with 48 filaments each. The core material was coated with a water-dispersible acrylic adhesive A by dipping so that the adhesive adhesion amount in the resulting adhesive article was 80 mg / m, and then dried at 80°C for 3 minutes to form an adhesive layer, thereby obtaining an adhesive article 1 (thread-like adhesive body 1).
[0046] <Example 2> An adhesive article 2 (thread-like adhesive body 2) was obtained in the same manner as in Example 1, except that the core material was a composite yarn made by bundling one 48-filament polyethylene terephthalate (PET) yarn (280 dtex, manufactured by Teijin Frontier Co., Ltd.) and three 48-filament polylactic acid yarns (280 dtex) together without twisting them.
[0047] <Comparative Example 1> A water-dispersible acrylic adhesive A was applied to the release liner so that the thickness after drying would be 30 μm. This was then attached to both sides of a polylactic acid film (Ecologe SA101, manufactured by Mitsubishi Chemical Corporation, thickness 50 μm), cut to a width of 1 mm, and the release liner was removed to obtain comparative adhesive article 1.
[0048] The adhesive articles obtained in the examples and comparative examples were evaluated as follows. [Adhesive strength] Using the adhesive article 40 obtained in the examples and comparative examples, a circular acrylic plate 42 having a thickness of 3 mm and a diameter of 70 mm was bonded to a rectangular polycarbonate resin plate 41 (short side 80 mm, long side 110 mm, thickness 10 mm) having a rectangular slit (short side 30 mm, long side 40 mm) in the center, so that the center of the acrylic plate 42 and the center of the slit of the polycarbonate resin plate 41 were aligned, and the adhesive article 40 was pressed for 10 seconds at 2 kg. As shown in Figures 3(a) and (b), the adhesive article 40 was arranged along the edge of the acrylic plate so as to have a length of 22 cm. A perspective view of the bonded state is shown in Figure 3(a), and a cross-sectional view of the AA line in Figure 3(a) is shown in Figure 3(b). Next, the polycarbonate resin plate 41 was fixed, and a load was applied through the slit to the center of the acrylic plate 42 in the direction in which the acrylic plate 42 and the polycarbonate resin plate 41 separated, as shown in Figure 3 (b), and the maximum load observed until the acrylic plate 42 and the polycarbonate resin plate 41 separated was measured and used as the adhesive strength (N / 22 cm).
[0049] [Biomass ratio] The biomass degree was calculated according to the following formula, assuming that the biomass degree of the PET yarn used in the core material was 0%, the biomass degree of the polylactic acid yarn was 100%, and the biomass degree of the water-dispersible acrylic adhesive A for the adhesive layer was 0%. Biomass content of thread-like adhesive bodies [%] = 100 × (mass of biomass-derived components contained in thread-like adhesive bodies [g]) / (total mass of thread-like adhesive bodies [g])
[0050] Furthermore, the thread-like adhesive bodies obtained in the Examples were evaluated for contact angle as follows. [Contact angle] The contact angle θ0 of water measured immediately after 2 μl of water was dropped onto the core material used in each example, and the contact angle θ of water measured 30 seconds after the drop 30 Difference between (θ0-θ 30 ) was calculated. The difference in contact angle (θ0-θ 30 As shown in FIG. 2, two 2 cm thick acrylic plates 3 are arranged with a gap of 3 cm between them, and a core material 2 is stretched straight across the gap on the top surfaces of these acrylic plates and attached with tape 4. Next, 2 μl of water is dropped onto the core material that spans the gap, and the contact angle of water θ0 immediately after the drop and the contact angle of water θ after 30 seconds have passed are measured. 30 was measured using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., product name "DropMaster"), and calculated from these values.
[0051] The results are shown in Table 1 below.
[0052] [Table 1]
[0053] As shown in Table 1, the thread-like adhesive body of the embodiment can be attached in a circular shape along the edge of the acrylic plate, and exhibits sufficient adhesive strength. In other words, an adhesive body with excellent strength and flexibility was obtained. Furthermore, an adhesive body with high biomass and low environmental impact was obtained. On the other hand, the adhesive article of the comparative example had poor flexibility and could not be attached in a circular shape, so that the adhesive strength could not be evaluated. [Industrial Applicability]
[0054] According to the present invention, it is possible to provide a thread-like adhesive material that ensures strength and flexibility while reducing the environmental load. [Explanation of symbols]
[0055] 10 Thread-like adhesive body 1 Adhesive layer 2 Core material 3 Acrylic board 4. Tape 40 Adhesive articles 41 Polycarbonate resin plate 42 Acrylic board
Claims
1. A thread-like adhesive body comprising a thread-like core material and an adhesive layer covering a surface of the core material in a longitudinal direction, The core material contains a biomass-derived component, The biomass ratio of the filamentous adhesive body is 35% or more; The thread-like adhesive body has a difference (θ 0 -θ 30 ) between a contact angle θ 0 of water measured immediately after 2 μl of water is dropped onto the core material and a contact angle θ 30 of water measured 30 seconds after the dropping, that is, 20° or less.
2. The thread-like adhesive body according to claim 1 , wherein the core material is a multifilament thread.
3. The thread-like adhesive body of claim 2 , wherein the multifilament yarn comprises filaments that do not contain biomass-derived components.
4. The thread-like adhesive body according to claim 2 or 3, wherein the multifilament yarn is twisted.
Citation Information
Patent Citations
Thread-like adhesive tool and production thereof
JP1991231980A
Polylactic acid-based sheet or film and method for producing the same
JP2009173715A
Polyalkylene terephthalate resin composition and fiber comprising same
JP2011219736A
Adhesive article
WO2019065886A1